An automatic domain updating method for fast 2-dimensional flood-inundation modelling. (June 2019) - Tanaka, Tomohiro; Tachikawa, Yasuto; Ichikawa, Yutaka; Yorozu, Kazuaki
Abstract: Flood-inundation modelling is essential for understanding flood dynamics and implementing flood risk management. Despite its increasing demands, it remains computationally expensive to perform 2-D flood-inundation simulations at large scales or fine spatial resolutions. This study presents a simple and novel algorithm for 2-D flood-inundation modelling, called the Automatic Domain Updating method, which dynamically updates the simulation domain of a 2-D flood-inundation model. The method limits the simulation domain where governing equations are solved to flooded areas in each time step by tracking the location of wet and dry interfaces. The proposed algorithm was tested in an actual river basin for different types of flooding. The results show that the ADU method regulates the simulation domain to flooded areas and slashes the computational time for grid-based 2-D flood-inundation simulations typically by 5%–20%, with correspond to the ratio of flooded area to the whole simulation domain.